Hubungan Kausalitas antara Keadilan Organisasional, Kepuasan Kerja, dan Komitmen Organisasional - Pareke, Fahrudin; Suryana, Popo (Jurnal Trikonomika, 2009)
The causal relationships among organizational justice, job satisfaction, and organizational commitment have long been investigated by scholars, academicians, and researchers. However, the researches in this field have poor evident due to structural model of the causality. The main goal of this research is to test the conceptual model of the relationships among organizational justice, job satisfaction, and organizational commitment, beyond the linear relationships that have investigated in the previous researches. Survey methods using questionnaire adopted for getting primary data from the respondents who are the faculty members of public and private universities in Bengkulu Provinces. Two-hundred-and-seventy-seven out of 321 respondents completed 54 item questionnaires distributed. Data were analyzed by Structural Equation Modeling (SEM). Results showed that the conceptual model of the relationships among organizational justice, job satisfaction, and organizational commitment has the reasonable goodness of fit. Furthermore, results also provide the strong evident that organizational justice positively affect the job satisfaction and organizational commitment; and job satisfaction positively affect the organizational commitment.